The Current Practice Applications of Artificial Intelligence to Improve Traffic Flow During Roadside Construction at Jalan Batu Pahat- Ayer Hitam- Kluang FT050 - Rohaizad, Aida Syakirah; Omar, Roshartini (Research in Management of Technology and Business, 2024)
In a traffic study done in 2020, it was discovered that there was 28,298 traffic in 16 hours and 2,279 traffic between the hours of 5 and 6 pm. Compared to other locations in the same district, the quantity of traffic on Jalan Kluang is the greatest in Batu Pahat. Higher incomes lead to more travel and car ownership, while growing commercial activity adds to service and freight traffic. These trends contribute to widespread traffic congestion, causing increased costs and productivity losses. The research objectives are to investigate current practices of Artificial Intelligence (AI) usage in traffic flow during roadside construction in Jalan Kluang, investigate factors of Artificial Intelligence (AI) usage in traffic flow during road construction in Jalan Kluang, and to determine challenges the adoption of Artificial Intelligence (AI) in traffic flow. In order to collect data for the study, a variety of primary and secondary methods are used, including literature reviews and interviews. Using the Google Meet application, three respondents from various agencies JKR Malaysia, Muda Consult Sdn Bhd and Aktif Unggul Sdn Bhd were interviewed as part of the qualitative approach. The research utilized a content analysis methodology to methodically evaluate the remarks provided by respondents, exposing the current applications of artificial intelligence (AI) for traffic flow management during roadside construction on Jalan Kluang. As a result of the research, respondents demonstrated the effectiveness of AI is in reducing traffic congestion in these kinds of scenarios such as Intelligent Transportation System (ITS) and machine learning and IOT. From the perspectives of these three respondents, it can be concluded that reducing risk, minimize time travel and lessen the traffic congestion are the main factors of artificial intelligence (AI) usage in traffic flow in Jalan Kluang. The study also found the main obstacles to the adoption of Artificial Intelligence (AI) in traffic flow during roadside construction at Jalan Kluang are high cost in installation with maintenance and for a smaller city, it might not practical require huge amounts of data to function effectively.